An Example of Art Management in Java: Art Management and Community Management Using Local Folk Art - Kaori Okado (Graduate School of Institut Seni Indonesia Yogyakarta, 2015)
In the present study, I examine the activities of a community network called Tlatah bocah at Mount Merapi and discuss their methods of art management and the benefit of them to the communities involved. They have been conducting festivals of folk performing arts for children and scholarship programs while very much respecting participants’ autonomy. Many benefits were gained by the communities involved. This kind of structure can be called “community management”. I demonstrate that this new system can add a new role and new value to traditional performing arts, empowering local communities.